ANALISIS KESULITAN BELAJAR DALAM MEMECAHKAN MASALAH FISIKA PADA MATERI HUKUM NEWTON TENTANG GERAK - Hijriani, Hijriani; Hatibe, H. Amiruddin (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
The purpose of this study was to determine students' learning difficulties in solving physics problems in Newton's Law of Motion. This research used a qualitative descriptive method which was conducted on the students of class X IPA 3 SMA Negeri 2 Sigi. Sampling was done by purposive sampling. The data in this study were collected through observation, written essay tests and interviews. Based on the results of the study, it can be concluded that the ability to solve physics problems on Newton's Law of Motion was classified as moderate category. Factors that affect the ability to solve problems or learning difficulties in physics, were: internal factors include students 'lack of interest in physics lessons, fatigue and students' lack of knowledge of Newton's Law of Motion material, students do not understand the questions well so they do not understand what the questions are asking , the use of formulas that are not precise and they do not check the completion and answer process. Meanwhile, external factors include family atmosphere, how to educate parents, parents' attention, social media, the applied curriculum and facilities to support the teaching and learning process in schools.